PERANCANGAN MOTIF BATIK MODERN TEKNIK CAP KERTAS DENGAN SUMBER IDE KERATON KASUNANAN SURAKARTA - Tutik Dwi Ambarwati (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Batik is a traditional cloth that has two types, namely traditional batik and modern batik. The Kasunanan Surakarta Palace is a symbol of the preservation of Javanese culture which has an implied meaning, one of the palace complexes that has a higher sacredness value than the surrounding buildings is Sitihinggil Lor. The design method that was used refers to Colin Clipson's thinking and uses the methods of observation, interviews, and visual studies. The design stage was chosen through the source of the idea for the decoration of the Surakarta Kasunanan Palace with the style of paper stamped batik. The results of the visualization of the selected designs will be continued in the process of paper stamping techniques made of art paper and art carton with synthetic coloring which then produces a long cloth or jarik that can be used in various formal and informal events.